PENERAPAN MEDIA PEMBELAJARAN BERBASIS YOUTUBE MENULIS KARANGAN PERSUASI PADA MATAKULIAH KETERAMPILAN MENULIS - Sakrim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
The process of teaching and learning in the current era or the era of digitalization leads to the use of electronic-based media. The use of various literacy teaching materials for educators and students can facilitate the teaching and learning process. There are still many findings in practice the teaching and learning process still uses media that is less desirable. For example, the use of LKS, powerpoint, and text-based books is still the main medium in the learning process. Therefore, the application of YouTube-based teaching media needs to be researched, as a solution and as a reference for future learning. The most basic reason is that YouTube-based media is media that is popular and easily accessible to the general public. This research was conducted in a writing skills course, especially writing persuasive sentences. In this study using qualitative methods by collecting data recorded, read, and recorded. The results of the research using YouTube-based teaching media are considered successful because students in carrying out assignments from the aspect of using persuasive sentences are very precise and correct. The message conveyed to the reader is easily understood by the reader. From the findings of data written by students, in addition to the messages conveyed it is easy for students to be motivated in the learning process so that they can increase their interest in learning higher.